2022
DOI: 10.1007/s00221-022-06336-4
|View full text |Cite
|
Sign up to set email alerts
|

Older adults can rely on an auditory cue to generate anticipatory postural adjustments prior to an external perturbation

Abstract: To minimize the potential postural disturbance induced by predictable external perturbations, humans generate anticipatory postural adjustments (APAs) using visual information about a perturbation. However, it is unknown whether older adults can generate APAs relying on auditory information. Ten older adults received external perturbations (a) with visual information but no auditory information available, (b) without neither visual nor auditory information, (c) with both visual and auditory information availab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 31 publications
1
2
0
Order By: Relevance
“…However, when the task is unexpected, APA is not optimized. The same reports have been confirmed for auditory cues, which, as a conditioning stimulus, can trigger APA in healthy individuals against an external perturbation in youth adult (26).…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…However, when the task is unexpected, APA is not optimized. The same reports have been confirmed for auditory cues, which, as a conditioning stimulus, can trigger APA in healthy individuals against an external perturbation in youth adult (26).…”
Section: Discussionsupporting
confidence: 67%
“…Visual information is usually serious to create effective APAs prior to postural disruption. Preceding studies similarly reported that healthy young adults could be dependent on an auditory cue to produce postural responses to outer perturbation (26). All the researchers stated that when larger APAs were produced for an external postural perturbation, less postural instability was detected.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation